REPRESENTATION OF WOMEN IN NEWS AND FEATURE PHOTOS: A STUDY ON SELECTED BANGLADESHI DAILIES - Deb, Soma (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
Visual representation becomes a mode of comprehending the world and news media are among the major carriers of visual image. How media represent women through texts and images are considered to be a key influence on people’s idea of women’s position in society. This research anchored on the theoretical lens of feminist media theory, media representation and media objectification theory, investigated how women are represented in news and feature photographs of Bangladeshi newspapers. This study has employed content analysis method for data collection. Two top circulation Bangladeshi national dailies, the Daily Star and the Prothom Alo, were chosen purposively. Newspaper copies of one year, for the period of 1st January to 31st December 2022, were chosen for the study. Following Stempel’s (1952) suggestion, researcher decided to scrutiny 24 issues of each newspaper, taking copies dated 2 and 16 of every month as sample. This study found that women are underrepresented and misrepresented in news and feature photographs. Even in the dailies, considered by many as prestige newspapers, women are rarely presented as protagonists in photos. Although improvements are noticeable in some aspects, news and feature photos still present women as negative, trivial and associate mostly with the private sphere (household and family life). Findings of the study validates the observation we found in previous researches that women continue to be marginalized in news and feature photos.